Ideational Metafunctions in Noah Kahan’s Stick Season Album: A Discourse Analysis - Sipayung, Naftalie Grace; Pratama, Rizky Mirani Desi (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2026)
This research analyzes the realization of metafunctions in selected songs from Noah Kahan’s Stick Season album using Halliday’s Systemic Functional Linguistics (SFL) framework. The study focuses on ideational metafunction and explores how language constructs meaning in song lyrics. A qualitative descriptive method was applied to five selected songs: Stick Season, All My Love, Strawberry Wine, Growing Sideways, and You’re Gonna Go Far. Data were collected from official lyric videos and analyzed at the clause level. Findings reveal that mental processes dominate the ideational metafunction, as seen in “I am terrified of weather ’cause I see you when it rains,” reflecting inner experiences.